Moral religion in Tolstoy’s religious philosophy and in W. Herrmann’s liberal theology - Maxim Pylaev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2019)
This article is intended to shed light on the transformations of Kantian ethical thought in theological ethics of W. Herrmann, one of the most prominent liberal theologists, and in theorising of religion in fi ction by L. Tolstoy. The main thesis of the article is that Christianity (the religion on the whole) in the framework of religiousphilosophical and theological cognition in Post-Enlightenment era is not able to make its essence explicit without addressing ethical topics. Herrmann did manage to propose an elaborate theological interpretation of Kant’s ethical substantiation of religion. This theologian linked the existence of moral law to the historical form of Revelation in the personality-related existence of its bearer. Employing F. Schleiermacher’s conception of religion, Herrmann analysed the functioning of the moral law in the ethical way of thinking of the empirical subject in such notions as faith, forgiving, love, salvation. Having proposed an exclusively moral interpretation of kerygma, Herrmann made it understandable to his contemporaries and at the same time preserved the unique character of the Christian message. Herrmann’s moral law becomes religion only through the bearer of Revelation, i.e. the person with high moral standards. While Schleiermacher unites transcendentalism with phychologism (as W. Dilthey wrote about this) in the conception of empirical religious feeling, Herrmann unites transcendentalism (Kant’s idea of the absolute moral law) with the historical Revelation in Jesus Christ. Belief in this person comes to be the beginning of the new, i.e. religious, life. In L. Tolstoy’s fi ction, Kantian understanding of religion intertwines, on the one hand, with a discourse similar to existential and philosophic and, on the other hand, with an interpretation of Christian ethics as the ethics of love for one’s neighbour through the idea of absolute non-resistance to the evil by force. Thus, the issue of the ethical substantiation of religion transcends not only the boundaries of Christian consciousness but also the limits of philosophy, the essence of which is determined by German idealism. Tolstoy’s ethical explanation of religion implies coherence with various types of religiosity as well as with various forms of philosophy. In other words, it confi rms the thesis about inexhaustible heuristic possibilities of explicating religious consciousness by means of moral categories.